The Effectiveness of Image Media to Improve Students' Poetry Writing Skills - Puspita*, Laurensia Elya; Monika, Santy; Ramli, Ratu (Universitas Syiah Kuala, 2023)
This study aims to describe the effectiveness of image media in improving poetry writing skills. The focus of the research is students' skills in writing poetry through image media with a pre-experimental design research type. The aim is to see the effectiveness of image media in improving students' skills in writing poetry through a group pretest-posttest design. In this study there was only one study group and no comparison group, only an initial test and a final test were carried out before and after using image media. The data in this research are the results of students' pretest and posttest scores. The data source is class XI students at SMKN 2 Merauke. After the data is obtained, it is then analyzed using descriptive statistical techniques and inferential statistics. The pretest results of students' poetry writing assignments without using image media are classified as low with an average score of 62. The post-test results of students' poetry writing assignments without using image media are classified as high with an average score of 86. The use of image media influences student learning outcomes and is effective in improving students' poetry writing abilities.